SOSIALISASI PERHITUNGAN SISA HASIL USAHA KOPERASI SEKOLAH DI KABUPATAN DELI SERDANG - Anggono, Anggono (JUBDIMAS ( Jurnal Pengabdian Masyarakat), 2025)
Cooperatives play a crucial role in Indonesia’s economic system, based on principles of kinship and aimed at improving the welfare of its members. However, the development of cooperatives, particularly in educational institutions, has been slow due to limited understanding of cooperative concepts among educational staff, teachers, and students. This study focuses on improving the understanding of Sisa Hasil Usaha (SHU) or Cooperative Surplus at SMA Swasta Maitreyawira Deli Serdang. The aim of this community service activity was to socialize and educate participants about SHU calculations, using the direct instruction method. The activity included the introduction of cooperative concepts and practical exercises in SHU calculation. The results showed significant improvement in the understanding of SHU, as seen from the pre-test and post-test comparison, with scores increasing for educational staff, teachers, and students. Despite challenges such as participant absenteeism due to official duties and tight schedules, the activity successfully met its goals. Recommendations include ensuring participant availability and extending the time for socialization for deeper learning.